What is the impact of nicotine pouches on oral health: a systematic review - Dulyapong Rungraungrayabkul; Piyada Gaewkhiew; Tippanart Vichayanrat; Binit Shrestha; Waranun Buajeeb (BMC, 2024)
Abstract Background Increase in nicotine pouch (NP) users, particularly among the young, is a matter of concern requiring a comprehensive understanding of its short- and long-term oral health implications. The objective of this research was to systematically review potential oral side-effects associated with NP usage. Methods This systematic review was conducted following the PRISMA guidelines. Databases (Medline via PubMed, Scopus, Cochrane Trial, and Google Scholar) were searched for relevant studies up to February 2024. Modified Newcastle-Ottawa Scale (NOS) and the Risk Of Bias In Non-randomized Studies - of Exposure (ROBINS-E) tool were used to assess the quality and bias of the included studies. Results Three studies were included for this review, two from Europe and one from USA, and considered of a total of 190 participants. All studies were deemed to have a high risk of bias. Participants used NP for periods ranging from 1 month to 10 years. Among these studies, only one study provided information on the usage pattern between 1 and 5 units for an average of 11 ± 7 min per session. Oral mucosal changes at the site of placement were common among NP users. Oral lesions varied from slight wrinkling to various white lesions, seemingly related to the NP units consumed per day and their duration of usage. Other oral side effects included dry mouth, soreness, gingival blisters, and a strange jaw sensation. Conclusions Research on the use of NP and its effect on oral health are currently limited. The use of NP should take into consideration the short-and-long-term effects, especially on oral health. Further studies are crucial to understand oral health implications associated with NP usage. Systematic review registration PROSPERO Registration number CRD 42,024,500,711.